Variações de preços no mercado imobiliário de Manaus e a formação de bolhas especulativas - Luiz Augusto de Carvalho Francisco Soares (2014)
The real estate market has , over the coming years , more precisely from 2008 - when it was influenced worldwide by the U.S. housing crisis had a burst bubble , behaving atypically with characteristic formation of these bubbles in various places the world. In Brazil , this marketsuffered all sorts of variations, caused by a series of government measures and other factors such as the arrival of foreign capital attracted by existing lasting economic stability. However, the feature of this market in specific Brazilian regions do not always reflect the national character , especially because these are not uniform . Manaus, capital of Amazonas state in northern Brazil , to be a very isolated market has its own characteristics and influences of other nearby markets and larger often different from the rest of the country . Notoriously spoken throughout the real estate market in this city of the presence of a speculative bubblethat would tend to "burst " after the world cup football 2014 . Given this fact and phenomenon, this study investigated the atypical variations of this real estate market between the periods of January 2008 to December 2013 , and investigated whether the seven cognitive failures described by behavioral finance in the price formation process of this market arepresent . For this we applied the concept of Shiller (2000 ) , which states that the process of bubble can be defined as a situation in which high prices are sustained largely by investors' enthusiasm rather than by consistent estimation of real value . In order to achieve this aim,four research techniques were applied. Two order to analyze the variation in house prices relative to inflation and two aimed to investigate the presence of cognitive failures described by behavioral finance literature. For the first was held a focus group sessions with two nine eight realtors respectively, and also analyzes the statistical variation in the prices of properties comparing with the same period inflation . For the second interview was conducted in depth with a professional in this key market and a questionnaire to the 22 dominant construction of Manaus market to detect such failures. After tabulated and analyzed the data obtained it wasobserved that the property market in Manaus behaved atypically between the years 2008-2013 and the existence of these cognitive failures in the decision making process of price setters, beeing cognitive failure of Social Influence more by this score formed.